Interaction between XRCC2 gene polymorphism and abdominal obesity on risk of endometrial carcinoma - Wenjuan Tian; Siyu Cao; Wei Zhang; Chenlian Quan; Meiqin Zhang; Yan Huang (Taylor & Francis Group, 2024)
AbstractAims The aim of this study was to investigate the impact of three single nucleotide polymorphisms (SNPs) within X-Ray Repair Cross Complementary Group 2 (XRCC2) gene and additional gene- abdominal obesity (AO) interaction with endometrial carcinoma (EC) risk.Methods Hardy-Weinberg equilibrium was tested for all participants by using SNPstats (online software: http://bioinfo.iconcologia.net/SNPstats). The best SNP-SNP and gene-AO interaction combination among three SNPs within XRCC2 gene and AO was screened using generalized multifactor dimensionality reduction (GMDR).Results We employed the logistic regression analysis showed that rs718282-T allele is associated with increased EC risk, adjusted ORs (95%CI) were 1.67 (1.23-2.04). However, we did not find statistical association between rs3218536, and rs3218384 and EC susceptibility. GMDR analysis was used for SNP-SNP- and gene-abdominal obesity analysis. The cross-validation consistency and the testing accuracy for the interaction were calculated. The two-locus model between rs718282 and AO had a testing accuracy of 60.11%, which was significant at the p < .001 level, and this two- locus model was considered as the best model. It provided statistical evidence for rs718282 gene-AO interaction effects. The results indicated that AO influenced the EC risk depending on the rs718282 genotypes. Compared with non- AO subjects with rs718282-CC genotype, AO subjects with rs718282-CT or TT genotype had the highest EC risk, OR (95%CI) was 2.83 (1.67 − 4.02), after covariates adjustment.Conclusions Both the rs718282- T allele, and its interaction with AO were associated with increased EC risk.